Risk premia in electricity wholesale spot markets: empirical evidence from Germany - Matthäus Pietz (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2009)
This paper contributes to the ongoing discussion on price formation in electricity markets. For this, we conduct an analysis of the German electricity wholesale spot market which is located at the European Energy Exchange (EEX). Our dataset covers three spot market segments, namely the intraday market, the block contract market and the day-ahead market. Data ranges from August 2002 to May 2009. As results we find significant positive risk premia, both in the block contract market and in the day-ahead market. The risk premia in day-ahead market contracts vary in magnitude and in sign throughout the day. Furthermore, we detect a term structure of risk premia during the sub-period in which all three market segments were simultaneously existent. When testing for seasonality in the risk premia, we find evidence for higher risk premia in the summer months. The hypothesis of a relation between the risk premia and the spot price variance and skewness has to be rejected.
Keywords: G13; L94; Q40; 330; Electricity; Intraday Market; Day-Ahead Market; Risk Premia; Risk Premium; Energiemarkt; Spotmarkt; Stromhandel; Risikoprämie; Stromtarif; Deutschland